2022
DOI: 10.1101/2022.09.30.510243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barcoding populations ofPseudomonas fluorescensSBW25

Abstract: In recent years evolutionary biologists have developed increasing interest in the use of barcoding strategies to study eco-evolutionary dynamics of lineages within evolving populations and communities. Although barcoded populations can deliver unprecedented insight into evolutionary change, barcoding microbes presents specific technical challenges. Here, strategies are described for barcoding populations of the model bacterium Pseudomonas fluorescens SBW25, including the design and cloning of barcoded regions,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The high-resolution colonization dynamics could also be extended by barcoding pathogenic species, such as P. aeruginosa and S. enterica, which are more aggressive colonizers than E. coli K12. Recently, the successful barcoding of Pseudomonas fluorescens SBW25, 84 demonstrates the potential applicability of our approach for generating a library of more than 10 5 barcodes. Additionally, our use of the Tn7 integration site, conserved among Gram-negative bacteria, suggests that our method could be easily extended to other bacteria in this group.…”
Section: Discussionmentioning
confidence: 92%
“…The high-resolution colonization dynamics could also be extended by barcoding pathogenic species, such as P. aeruginosa and S. enterica, which are more aggressive colonizers than E. coli K12. Recently, the successful barcoding of Pseudomonas fluorescens SBW25, 84 demonstrates the potential applicability of our approach for generating a library of more than 10 5 barcodes. Additionally, our use of the Tn7 integration site, conserved among Gram-negative bacteria, suggests that our method could be easily extended to other bacteria in this group.…”
Section: Discussionmentioning
confidence: 92%
“…This check was made by sequencing across the Tn7 insertion site in 96 independent clones. The resultant data showed that all 96 contained unique barcodes [see (Theodosiou et al 2023)].…”
Section: Design and Construction Of Barcoded Integrative Plasmidsmentioning
confidence: 99%